How will global trade patterns evolve in the long run? - Eddy Bekkers; Erwin L. Corong; Jeanne Métivier; Daniil Orlov (World Trade Organization (WTO), 2023)
In this paper the evolution of global trade patterns until 2050 is projected with a recursive dynamic computable general equilibrium (CGE) model. Feeding the model with exogenous projections on macroeconomic, demographic, sectoral and trade cost variables, the evolution of trade patterns emerges endogenously from the model. The approach is innovative in both modelling approach and exogenous inputs. GDP growth emerges endogenously in the model because of diffusion of ideas as a result of international trade and trade cost changes are based on estimates of technology and trade policy changes. The projections indicate that (i) because of projected reductions in trade costs, trade will grow more than GDP, generating a global trade-toGDP growth rate of 1.1; (ii) because of structural change, the global share of manufacturing trade falls from 64% in 2020 to 52% by 2050, whereas the share of services trade rises substantially from 24% to 38%; (iii) because of technological catch-up, the share in global trade of both developing and least-developed countries (LDCs) will rise (with developing countries overtaking developed economies around 2035), the share of intra-developed country trade will fall, whereas the share of intra-developing country trade and those between developing and developed countries will rise.
Keywords: F17; D58; 330; Global trade patterns; long-run projections; dynamic CGE models